2022
DOI: 10.29374/2527-2179.bjvm005221
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic's impact on the practices and biosecurity measures of veterinary medicine professionals in Brazil

Abstract: Veterinarians, among other health professionals, are considered health professionals at high risk of exposure to and contraction of COVID-19. The main objective of this study is to assess changes in the clinical practices of veterinarians during the COVID-19 pandemic around prophylactic and biosafety measures, as well as to evaluate changes in workload and cost-benefit ratio. An online questionnaire was sent to veterinary professionals from July 2020 to July 2021 using Google Forms. A total of 1134 veterinaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…On the other hand, a study conducted in different Brazilian states found that during the pandemic, most veterinarians adopted biosecurity measures to protect themselves, team members, and patients, increasing the use of masks, face protectors, and TNT coats. Most important, Veterinary medical care was considered an essential activity in Brazil (Barreto et al, 2022). The results herein presented are important to understand how COVID-19 affected the dairy sector in Brazil, and how in future cases of sanitary problems, the Govern can mitigate issues in the sector to prevent economic losses together with preserving human and animal health.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, a study conducted in different Brazilian states found that during the pandemic, most veterinarians adopted biosecurity measures to protect themselves, team members, and patients, increasing the use of masks, face protectors, and TNT coats. Most important, Veterinary medical care was considered an essential activity in Brazil (Barreto et al, 2022). The results herein presented are important to understand how COVID-19 affected the dairy sector in Brazil, and how in future cases of sanitary problems, the Govern can mitigate issues in the sector to prevent economic losses together with preserving human and animal health.…”
Section: Discussionmentioning
confidence: 90%
“…[23][24][25][26][27][28][29][30][31][32][33] Therefore, personal safety of medical personnel is important for prevention and control. [34][35][36][37][38][39][40][41][42][43][44][45] According to the relevant documents, guidelines and other materials and the working experience of the designated hospital, and in combination with the current situation of the existing sites, equipment, facilities and personnel of the Department, the corresponding prevention, and control plan is formulated. [46,47] From the perspective of the laboratory, this paper discusses how to do a good job in biosafety protection, improve biosafety protection measures, and optimize the workflow.…”
Section: Introductionmentioning
confidence: 99%